(untitled) (Minerva. Revista de Filología Clásica, 2019)
The recipe T 22-27 for preparation of purple-dye in the so-called Compositiones ad tingenda_musiva begins as follows: ’Conquilium nascitur in omne mare, plus quam in insula in his lacis’. The untenable reading lacis should probably be restored to lacis (= pelagis), taking into account both the balance of the text and that pelagia was the name of a kind of purple-fish according to Pliny the Elder (nat. ix. 131).